Rhetoric and social relations : dialectics of bonding and contestation - Abbink, J.; LaTosky, Shauna (Studies in rhetoric and culture, 2021)
"This volume explores the constitutive role of rhetoric in socio-cultural relations, where discursive persuasion is so important, and contains both theoretical chapters as well as fascinating examples of the ambiguities and effects of rhetoric used (un)consciously in social praxis. The elements of power, competition and political persuasion figure prominently. It is an accessible collection of studies, speaking to common issues and problems in social life, and shows the heuristic and often explanatory value of the rhetorical perspective"--